Critical role and effectiveness of leadership on Organizational performance in Malaysia. - Sadeghi, Zahra; Farid, Hadi (2011)
Leadership offers a direction and assists in bringing success of an organization. It contributes to achieve the mission of organization and thus, it can understand truly how exactly it can help to this process. The role of leadership in Human Research Development can have effect on the performance of organization. It customizes the programs and makes the required designs to facilitate the challenges of leadership. Directing companies through the changes of competitive landscape is a big and an effective process in any country and Malaysia is not an exception. Many people are working all around the world to access and achieve the specific objectives with the essential support of a leader. Leaders try to set their beliefs to achieve the success and goals. Skill and knowledge are two important features that are needed to execute an effective lead. All leaders need to fulfil 4 distinguished roles: the visionary, the tactician, the facilitator, and the contributor. The objective of this paper is to investigate the leadership development based on different factors such as skill, confidence and their relation with performance in an organization and one theory which is termed as transformational theory.